2014
DOI: 10.2535/ofaj.91.49
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between findings of mandibular cortical bone in inferior border and bone mineral densities of lumbar vertebrae in postmenopausal women

Abstract: Summary: It is important to assess the general bone condition in dental implant treatment. The relationships between the bone mineral densities (BMDs) of lumbar vertebrae and mandibular cortical bone condition in the inferior border using multi-slice computed tomography (CT) were assessed in postmenopausal women. If a strong correlation between them is obtained, the mandibular cortical bone condition may be useful to evaluate the general bone condition. Twenty-two postmenopausal women were enrolled in this inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Also, measurement of the mandibular cortical bone width (MCW) at the inferior border on panoramic radiography was useful for the screening of osteoporosis 16) . A weak correlation was observed between MCW-MSCT using multi-slice CT and the percentage of the young adult mean (YAM) in the lumbar vertebrae 7) . A threshold voxel value must be set in conebeam CT to evaluate MCW; however, voxel values obtained from cone-beam CT are not absolute 17) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, measurement of the mandibular cortical bone width (MCW) at the inferior border on panoramic radiography was useful for the screening of osteoporosis 16) . A weak correlation was observed between MCW-MSCT using multi-slice CT and the percentage of the young adult mean (YAM) in the lumbar vertebrae 7) . A threshold voxel value must be set in conebeam CT to evaluate MCW; however, voxel values obtained from cone-beam CT are not absolute 17) .…”
Section: Discussionmentioning
confidence: 99%
“…Correlation coefficients between BMDs of the lumbar vertebrae and values using quantitative ultrasound densitometry ranged from 0.433 to 0.640 10) . In previous studies, the BMD of the third cervical vertebra and MCI-MSCT were proposed to evaluate the influence of the general bone condition in imaging diagnosis for dental implant treatment using multi-slice CT 6,7) . Celenk and Celenk reported that the relationship between the age and CT values of the fifth cervical vertebra was negatively correlated (r = 0.354) in the total subjects, with 68 men and 46 women, using a linear equation (y=-2.06x+485.86) 11) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lumbar vertebra is a hypersensitive site that is susceptible to bone injury (33). In clinical practice, kidney transplant recipients have a lower lumbar spine trabecular bone score, which is associated with an increased incidence of fractures (34).…”
Section: Discussionmentioning
confidence: 99%